Harmonic measurement techniques and passive filter design / Nor Azmi Mohd. Nor - Mohd Nor, Nor Azmi (1993)
This project is to study the various method used for measuring the harmonic contents caused by harmonic generating loads. A method and instruments used will then be chosen to determine the harmonic content of fluorescent lamp ballasts. The ballasts that control the operation of fluorescent lamps have been known for generating peak currents and introduce harmonic currents into the distribution system. To eliminate or reduce the harmonic content, passive filters will then be designed using appropriate design method.